The Significance of Immunohistochemical Markers in the Treatment of Breast Cancer - Nurov Jamshid Raxmatovich; Narzieva Dilnoza Fakhriddinovna (International Journal on Orange Technologies, 2021)
Breast cancer is a serious medical and social problem for most developed countries of the world. Immunohistochemical studies were performed on primary tumors of 70 breast cancer patients with different subtypes. An immunohistochemical study allows us to evaluate the indicators associated with the tumor cell cycle. Knowledge of immunohistochemical markers allows us to develop an optimal model for evaluating and choosing tactics for the treatment of breast cancer.